HUBUNGAN ANTARA KEBIASAAN MEROKOK DENGAN KEJADIAN ISPA PADA REMAJA DI DESA SIDODADI - Siti Patonah, Siti Patonah (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2014)
Smoking is a habit that can lead to dependence and also includes a major risk factor for the occurrence of respiratory disorders . Having ever smoked a big risk to suffer such pain Acute Respiratory Infection ( ARI ) can also weaken the energy and stamina of a person. The purpose of this study was to analyze the relationship between smoking and incidence of respiratory frequency in adolescents in the village Sidodadi . The design of this study is an analytic survey with cross sectional approach . Samples taken as many as 89 respondents using simple random sampling that all adolescents who smoked in the village Sidodadi . The research data was taken using a questionnaire , tabulated and tested Spearman 's rho correlations . The results showed that the respondents were in the habit of smoking as many as 42 ( 47.2 % ) , the frequency of respiratory events infrequently as many as 8 ( 19.0 % ) , the frequency of occurrence of ARI was 30 ( 71.43 % ) and frequency of occurrence often ARI 4 (=0.000 (r 9.5 %),with a value of < = 0.05 ) . The final conclusion is that there is a significant association between smoking and incidence of respiratory frequency in adolescents . Teens who have a habit of smoking should reduce / eliminate the smoking habit , because often smoking can cause respiratory infection . Keywords : Smoke , ARI